Energy Cooperation – The Strength of the Eu’s Economic Development - Francesco Ruggiero; Liviu Bogdan Vlad; Gheorghe Vlăsceanu; Alexandru Gavris; Dragos Vasile (Amfiteatru Economic)
Continuous economic development of the European Union countries has reached a stage in which both intra- and inter-state cooperation together with the interaction of economic actors, have become biggest strength. The present paper analyze the level of cooperation between European Union countries and the European Union policies in the energy field to emphasize a better image of the European Union energy security level and its future geopolitical trends. In spite of numerous consensus problems among Member States towards a unitary common direction, every state appears to have the same objective – to secure its economic development through energy. As such, the centre of economic gravity in the European Union countries has to be energy cooperation and all policies should be focused on it.